ТРИВИМІРНЕ МОДЕЛЮВАННЯ ЕЛЕКТРОМАГНІТНИХ І ГІДРОДИНАМІЧНИХ ПРОЦЕСІВ У ВІДБИВНІЙ ПЕЧІ ДЛЯ АЛЮМІНІЮ З ЕЛЕКТРОВИХРОВОЮ КАМЕРОЮ - Пеньковий, Т.О.; Бондар, О.І.; Гориславець, Ю.М. (Інститут електродинаміки Національної академії наук України, 2024)
On the basis of the developed mathematical model, a three-dimensional numerical study of electromagnetic and hydrodynamic processes was carried out in a reverberatory melting furnace with an electric vortex chamber in the form of a cylindrical chamber with a curve inductor, which performs two functions: it stirs the molten metal in the furnace bath and immerses the crushed metal scrap in the melt and then transports it to the melting bath. The influence of the height of the connecting channels and the angle of connection to the chamber of the pressure channel on three integral parameters is investigated: the average velocity of the metal in the furnace bath, the melt flow through the cross section of the channels, and the average angular velocity of the metal in the vortex chamber. As a result of the simulation, it was established that with the growth of the relative height of both channels, the first two parameters that characterize the chamber as an electromagnetic stirrer of metal in the furnace bath increase, and the third parameter that defines it as a device for immersing scrap, decreases. As for the angle of connection of the pressure channel, the opposite is true here - with an increase in the angle, the average velocity of the melt in the furnace bath and its flow through the channels decrease, while the average angular velocity of the metal in the chamber increases. It was concluded that in practice it is necessary to find (choose) such compromise values of the height of the channels and the angle of their connection, which would ensure the implementation of both specified functions at a given level. Ref. 8, fig. 7.